Microbial metal respiration : from geochemistry to potential applications - Gescher, Johannes; Kappler, Andreas (Springer, 2013)
This book discusses the implications of dissimilatory metal reduction in microbiology, biochemistry and geochemistry, and such developments as the discovery of potential applications of dissimilatory metal reducers in bioremediation and microbial fuel cells